Obcy i swoi. Polacy w cyklu Czerwone Koło Aleksandra Sołżenicyna - Sidor, Monika (Acta Polono-Ruthenica, 2018)
The cycle of novels The Red Wheel, one of the most significant and yet least-known works of Alexandr Solzhenitsyn, offers a profound insight into the issue of national identity and relationships between Poles and Russians. The analysis of how Solzhenitsyn depicted Poles in the cycle, in terms of their being strangers or own people, is all the more interesting for the fact that it relates to a specific point in history. Indeed, in The Red Wheel novels, Solzhenitsyn provides a detailed description of the period of decline of the multinational Russian Empire, which, by extension, was a pivotal time in the history of the Polish quest for independence.